Meningkatkan Self Awareness Remaja Melalui Edukasi Mengenal Diri Sendiri di SMA Negeri 2 Playen - Azahira; Siregar; Wulandari; Putri; Ananda; Pratama; Afriansyah; Afrianingsih; Wally; Al-Pasyah (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
This activity is designed to provide support to high school students in overcoming challenges related to self-identity in this day and age. The goal is to give them a deeper insight into themselves, which includes their strengths, weaknesses, and potentials, so that they are able to make wiser decisions regarding their future education and career. The method applied was an interactive socialization with the theme “Learning About Yourself” held at SMA Negeri 2 Playen, Gunungkidul, Yogyakarta. This activity involved 50 students who were divided into three groups: class X, XI, and XII. Each group received materials as well as practical sessions focusing on self-reflection and potential mapping techniques. The results of this activity showed that all participants from the three groups-grade X, XI, and XII-showed a marked improvement in their self-understanding. Around 50 students actively participated in the discussion and practice sessions. The main benefit gained was increased self-awareness, which helped students to more clearly recognize their interests and talents. This is very helpful in determining the most suitable educational path and career choice for them. In conclusion, this activity proved that intervention through planned socialization is effective in increasing students' self-awareness. The active involvement of the students in this activity is crucial to help them build a solid foundation for their future. The active involvement of students in this activity is essential to help them build a solid foundation in planning their future